Ventilation and Cooling System for HXD3C AC Drive Electric Locomotive - SUI Xi-zheng; DENG Ji-chen (机车电传动)
Ventilation and cooling system of HXD3C AC drive electric locomotive was introduced from main consisting components, structural characteristics, capability parameter etc, which adopted highly integrated and modularized design idea to improve the ventilationcooling performance, reduce weight, and make overall locomotive design more reasonable.